Further Elucidation of Galactose Utilization in Lactococcus lactis MG1363 - Solopova, Ana; Bachmann, Herwig; Teusink, Bas; Kok, Jan; Kuipers, Oscar P. (Frontiers in Microbiology, 2018)
Since the 1970-ies, galactose metabolism in Lactococcus lactis has been in debate. Different studies led to diverse outcomes making it difficult to conclude whether galactose uptake was PEP- or ATP- dependent and decide what the exact connection was between galactose and lactose uptake and metabolism. It was shown that some Lactococcus strains possess two galactose-specific systems – a permease and a PTS, even if they lack the lactose utilization plasmid, proving that a lactose-independent PTSGal exists. However, the PTSGal transporter was never identified. Here, with the help of transcriptome analyses and genetic knock-out mutants, we reveal the identities of two low-affinity galactose PTSs. A novel plant-niche-related PTS component Llmg_0963 forming a hybrid transporter Llmg_0963PtcBA and a glucose-specific PTS are shown to be involved in galactose transport in L. lactis MG1363.